THE VOICE OF â€œDISSOCIATIVE IDENTITY DISORDERâ€ IN STRAWBERRY SPRING BY STEPHEN KING - Liana, Era Maret (JURNAL LITERARY CRITICISM, 2019)
The research will be discussing Psychology aspect especially in mental illness that is Dissociative Identity Disorder in the main character in Stephen King?s short stories. Dissociative Identity Disorder by DSM-IV (American Psychiatric Association, 1994:477) is a condition by the presence of two or more identities or personality. This Condition recurrently takes the individual's control behaviour and accompanied by an inability to remember important individual information called forgetfulness. The purpose of this research is to find some evidence that the main character of this short story really has Dissociative Identity Disorder syndrome there are come from behaviour, saying and etc. People who have Dissociative Identity Disorder syndromealso have some characteristic such as Forgetfulness, Depression, Trauma, and e.tc. This research is based on Strawberry King short stories, journal and some article become the reference for the theory. This research has obtained the result of how the main character?s in this short story face up some difficult conflict while he has turned into another personality. Keywords: Dissociative Identity Disorder, Trauma, Forgetfulness, Fog.